InCIEC 2013 Proceedings of the International Civil and Infrastructure Engineering Conference 2013 - Hassan, Rohana; Yusoff, Marina; Ismail, Zulhabri; Amin, Norliyati Mohd.; Fadzil, Mohd Arshad; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2014)
The special focus of this proceedings is to cover the areas of infrastructure engineering and sustainability management. The state-of-the art information in infrastructure and sustainable issues in engineering covers earthquake, bioremediation, synergistic management, timber engineering, flood management and intelligent transport systems. It provides precise information with regards to innovative research development in construction materials and structures in addition to a compilation of interdisciplinary finding combining nano-materials and engineering.
Timber Engineering -- Concrete Waste and Earthquake Engineering -- Flood Management and Intelligence Development -- Fluvial And River Engineering Dynamics -- Transportation Systems, Infrastructure and Intelligent Transport -- Geotechnical Engineering -- Innovative Construction Materials & Structures -- Bioremediation and Engineering -- Synergistic Innovative Management -- Nano-Materials for Engineering.
Keywords: Engineering; Civil engineering; Biotechnology; Materials; Engineering; Civil Engineering; Environmental Engineering/Biotechnology.; Water Industry/Water Technologies; Structural Materials